ANALYSIS OF COFFEE ROASTING PROCESS IMPROVEMENT AT SMALL COFFEE USING SEVEN TOOLS AND TRIZ METHOD - Anggoro Lanjar Siswanto; Amelia Nur Fariza; Decut Della Oganda (RADJA PUBLIKA, 2025)
This study aims to improve the quality of the coffee roasting process at Small Coffee, an MSME located in Cikarang, by applying the TRIZ (Theory of Inventive Problem Solving) method and the Seven Tools of Quality Control. The roasting process often faces defects in coffee beans, such as unripe, broken, and burnt beans, which reduce product quality and customer satisfaction. To determine the root causes and influencing factors, the study utilized a fishbone diagram, affinity diagram, and scatter diagram. These tools helped identify critical process inefficiencies and quality issues. Subsequently, the TRIZ method was employed to propose innovative solutions that resolve contradictions in the roasting process without creating new problems. The proposed improvements are expected to enhance process efficiency, lower the defect rate, and ensure consistent product quality. Moreover, the implementation of these solutions provides tangible benefits for Small Coffee and serves as a model for other MSMEs in the coffee industry aiming to boost their competitiveness and long-term sustainability. This research highlights the synergy between systematic problem-solving tools and innovation frameworks in optimizing small-scale industrial processes.